2012
DOI: 10.4046/trd.2012.72.5.426
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Varenicline and Abstinence Rates for Quitting Smoking in a Private Health Promotion Center-Based Smoking Cessation Clinic

Abstract: BackgroundVarenicline is an effective smoking cessation aid. However, smokers prescribed with varenicline do not always receive varenicline for 12 weeks, as recommended. This study analyzed the subjects who received varenicline and investigated the effect of varenicline treatment duration on the success rate of 6-month smoking cessation.MethodsThis study retrospectively analyzed 78 subjects, who received varenicline, out of the 105 smokers that had visited the smoking cessation clinic after medical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(18 reference statements)
1
9
0
1
Order By: Relevance
“…The proportion of the patients having experienced the side-effects of varenicline was 24.0%. This was similar to the findings of Song et al 13) (32.3%) and Lee et al 14) (30.8%). That nausea was the most frequently experienced side-effect was also consistent with the findings of the other studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The proportion of the patients having experienced the side-effects of varenicline was 24.0%. This was similar to the findings of Song et al 13) (32.3%) and Lee et al 14) (30.8%). That nausea was the most frequently experienced side-effect was also consistent with the findings of the other studies.…”
Section: Discussionsupporting
confidence: 92%
“… 6 7 8) The study published by the South Korean primary medical treatment center in 2012 also reported that the success rate of smoking cessation for 7 days in the 6th month among the patients who had taken the medicine for more than 12 weeks was 63.6%. 14) …”
Section: Discussionmentioning
confidence: 99%
“…The fact that relapse tends to occur early during a quit attempt (34) suggests that the first weeks of treatment are most important, but no firm conclusions can be drawn from the available literature. Identification of a minimum treatment duration (or amount of medication taken per day) for pharmacotherapy to be effective is important in order to design interventions that may increase adherence (35)(36)(37)(38).…”
Section: Suggestions For Future Researchmentioning
confidence: 85%
“…Proper adherence to smoking cessation pharmacotherapy is known to be low, even in general population samples of smokers, due to issues such as difficulty remembering to take the medication, managing side-effects, and following dosing instructions (Balmford, Borland, Hammond, & Cummings, 2011; Catz, et al, 2011; de Dios, Anderson, Stanton, Audet, & Stein, 2012; Etter & Schneider, 2013; Grassi et al, 2011; Hays, Leischow, Lawrence, & Lee, 2010; Lee et al, 2012; Liberman et al, 2013; Swan et al, 2010). Smoking cessation treatment clinical trials among methadone maintained smokers, specifically, have shown poor adherence to smoking cessation pharmacotherapy, and that pharmacotherapy adherence is related to smoking cessation outcomes (Richter, et al, 2005; Stein, Anderson, & Niaura, 2006; Stein, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%